2015
DOI: 10.1371/journal.pone.0129887
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Dispersal and Foraging Behavior of Entomopathogenic Nematodes in the Absence and Presence of Mobile and Non-Mobile Hosts

Abstract: Entomopathogenic nematodes have been classified into cruisers (active searchers) and ambushers (sit and wait foragers). However, little is known about their dispersal and foraging behavior at population level in soil. We studied lateral dispersal of the ambush foraging Steinernema carpocapsae (ALL strain) and cruise foraging Heterorhabditis bacteriophora (GPS11 strain) from infected host cadavers in microcosms (0.05 m2) containing Wooster silt-loam soil (Oxyaquic fragiudalf) and vegetation in the presence or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 59 publications
1
30
0
Order By: Relevance
“…Some ambushing Steinernema species also jump, where the IJ stands on its tail, curls, and propels itself into the air [6]. In general, ambushers are most effective at targeting motile hosts, while cruisers are most effective at targeting non-motile hosts [7]. However, recent studies suggest that many species are capable of engaging in either ambushing or cruising depending on the environmental context.…”
Section: Host Seeking By Entomopathogenic Nematodesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some ambushing Steinernema species also jump, where the IJ stands on its tail, curls, and propels itself into the air [6]. In general, ambushers are most effective at targeting motile hosts, while cruisers are most effective at targeting non-motile hosts [7]. However, recent studies suggest that many species are capable of engaging in either ambushing or cruising depending on the environmental context.…”
Section: Host Seeking By Entomopathogenic Nematodesmentioning
confidence: 99%
“…The extent to which Ste. carpocapsae moves in the soil also depends on which insect hosts are present [7, 9]. In addition, all EPN species examined so far exhibit robust chemotaxis in the presence of insect-derived odorants [10, 11].…”
Section: Host Seeking By Entomopathogenic Nematodesmentioning
confidence: 99%
“…Likewise, various biotic and abiotic factors can affect movement behavior (Perony and Townsend, 2013) such as group size (Bonnell et al 2013), environmental spatial structure and resource availability (Reeve and Cronin 2010), avoidance of predators (Beauchamp, 2017) and genetic diversity (Johnson et al 2016). Bal and Grewal (2015) found that the cruise foraging H. bacteriophora differ in its dispersal and foraging behavior from ambush foraging S. carpocapsae at the population level, and this behavior is affected by both the presence and absence of hosts and by their mobility. Ruan et al (2018) reported that EPN dispersal continuously exhibited an aggregative pattern (independent movement was not observed).…”
Section: Resultsmentioning
confidence: 96%
“…To minimize variation in WSS densities [21], plots were arranged linearly approximately equal distances from the edges of the fields. Individual plots were spaced ~8.0 m apart to avoid effects from overspray or migration of EPNs and plot order was randomized at each location [37]. …”
Section: Methodsmentioning
confidence: 99%